Analisis Dan Perancangan Sistem Informasi Layanan Pengadaan Barang Dan Jasa Metode Pengadaan Langsung Pada Dinas Pendidikan Provinsi Jambi - Santoso, Heri; Mulyono, Herry (LPPM Universitas Dinamika Bangsa, 2018)
Currently the process of procurement of goods and services with methods of direct procurement at the Jambi Provincial Education Office is still not optimal, this happens because the data is still in Microsoft Word and Microsoft Excel formats and is stored in an irregular folder, resulting in delays in file checking and contract making. Therefore, the authors design information system for procurement service, the authors provide solutions in the form of designing information system prototypes of goods and services procurement service. Where the system modeling used is UML (Unified Modeling Language). From the UML model can be formed interface design and table design that will facilitate the system implementation process. It is expected that the next researcher can be developed by adding an Android-based system design